Environmental, combustion, and performance investigation of low viscous biofuel in port fuel injection spark‑ignition engine - Karthick, C.; Chatterjee, Dipankar; Gupta, Nidhish; Saxena, Prakhar; Sivagami, K.; Jeevanantham, A. K.; Kasianantham, Nanthagopal; Shaik, Saboor; Asif, Mohammad; Khan, Sher Afghan; Ağbulut, Ümit (Springer Nature, 2023)
To avoid the food vs. fuel debate, other than food-based products, agricultural products are effective sources for fuel development. Various parts of plants and trees are used to produce sustainable, low-viscous biofuels, which are gaining much attraction due to their superior burning abilities. The turpentine biofuel produced from pine tree oil has been used for gasoline engines because of its better calorific value and other notable benefits. An attempt has been made to investigate the suitability of turpentine biofuel as a 50% replacement for gasoline in automotive applications to identify the optimum blend ratio. In this study, the experiments are conducted in the port-fuel-injected gasoline engine at different loading conditions of 0 kg to 15 kg at 1800 rpm. Using turpentine blends in a port-fuel-injected SI engine, performance characteristics have been observed with up to a 3–5% improvement in brake thermal efficiency and fuel economy for all concentrations of turpentine biofuel due to their higher calorific value. However, the implementation of turpentine biofuel has shown remarkable reductions in unburnt hydrocarbons by 50% and carbon monoxide emissions by 90% due to its superior burning ability. However, this reduction is not witnessed in oxides of nitrogen and carbon dioxide emissions due to the lower octane number and higher viscosity, which result in a 30% and 5% increase, respectively. Interestingly, the combustion characteristics are observed to be better at part load operations for lower concentrations (30%) of turpentine biofuel in the blends, and this trend has not been noticed at higher concentrations of turpentine biofuel. Finally, it has been concluded that turpentine biofuel would be a better option for partial gasoline replacement by up to 30%. However, for further investigation, the anti-knocking characteristics of the turpentine biofuel need to be improved, especially in 40% and 50% turpentine biofuel blends using suitable anti-knocking agents.